Substâncias para o controle de Meloidogyne incognita - Lopes, Karina Campos (2015)
The root-knot nematodes cause huge losses to many farmers around the world, and they are responsible for reducing production and commercial value of many agricultural products. Among these plant parasites there is the Meloidogyne incognita species, which stands out due to its broad adaptation to various environmental conditions and inefficiencies in its control methods. Although there are many studies trying to develop new methods to combat this phytoparasite, none of them has yet resulted in a procedure not pollutant, economically feasible and efficient in all agronomic situations, simultaneously . Consequently, investment in research in this area is imperative so that new methods to control M. incognita can be developed. An interesting possibility to meet this demand is using natural substances active against nematodes as starting points for the search for similar substances with greater nematicidal activities than those observed in natural substances. Therefore, in this work , in vitro assays were used to study the nematicidal activities of 35 substances similar to dihydrouracil and 9H-purine, because these substances proved to be active against Meloidogyne exigua in a previous work. Among the studied substances, it was observed that 2-pyrazinecarboxylic acid (15), 5-methyl-2-pyrazinecarboxylic acid (16), orotic acid (14), 2,3,5-triphenyltetrazolium chloride (35), methyl pyrazinecarboxylate (17), and 2,4-diaminopyrimidine (13) caused, respectively, the following immobility and mortality of second stage juveniles (J2) of M. incognita: 98.8 and 91.9%, 92.7 and 89.3%, 90.1 and 88.5%, 90.7 and 81.8%, 71.4 and 68.5%, 66.3 and 64.6%. When subjected to an assay with tomato plants (Solanum lycopersicon cv. Santa Clara) inoculated with M. incognita, substances that most resembled carbofuran (2,3-dihydro-2,2-dimethyl-1-benzofuran-7-il N-methylcarbamate) were 13, 35 and 16, which reduced the numbers of nematode eggs and galls to less than 52, 51 and 26%, 55, 19 and 31%, respectively, of that observed for the negative control, which was the vehicle used to dissolve the samples. Thus, 13, 35 and 16 are promising substances to control M. incognita.